A self-immolative near-infrared probe based on hemi-benzothiazolecyanine for visualizing hydrogen peroxide in living cells and mice. (February 2021) - Gong, Yi−Jun; Feng, Dan−Dan; Liu, Wei−Ning; Fang, Jing−Kun; Feng, Suling
Abstract: Hemicyanine dyes including hemi-indocyanine and hemi-benzindocyanine have been attracted considerable attentions to develop near infrared probes for in vivo fluorescence imaging. However, hemi-benzothiazolecyanine dye (MTR ) is rarely reported for detection analytes. In this work, to extend the sensing applications of MTR, we present an optimized route for facile preparation of the dye. And as a proof-of-concept, a self-immolative NIR probe MTR-HH based on hemi-benzothiazolecyanine dye was designed and synthesized for H2 O2 . The probe exhibited a 284-fold fluorescent enhancement to H2 O2 with a detection limit of 0.32 μM over other biospecies. Moreover, MTR-HH was successfully applied for visualizing endogenous H2 O2 in living cells and mice. Graphical abstract: Image 1